Analisis persepsi guru Indonesia terhadap sekolah sebagai organisasi belajar di era pandemi Covid 19 - Baharuddin Baharuddin; Yuyun Elizabeth Patras; Donna Sampaleng; Rais Hidayat (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Schools need to become learning organizations in order to be able to deal with various changes such as the current COVID-19 pandemic. Information about school as a learning organization for policy makers is needed to improve it. This reseach aims to find school instruments as learning organizations and at the same time recommend strategic findings for improving schools as learning organizations. The research began with a theoretical study to obtain content validity, continued with expert validity, readability trials, and finally the distribution of the instrument via online addressed to teachers in Indonesia. The research data used 1200 of 1211 respondents obtained by purposive sampling. Based on testing using the Rasch Model, this research found 12 instrument items to examine schools as learning organizations and recommended two findings to improve schools as learning organizations, namely: (i) improvements in aspects of teacher facilitation to get education and training, and (ii) giving rewards. to outstanding teachers.